2015
DOI: 10.3906/sag-1402-49
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of transcatheter aortic valve implantation on QT dispersion

Abstract: Background/aim: Electrophysiological changes are observed following mechanical stretches due to pressure overload in patients with severe aortic stenosis (AS). The electrical instability occurs after depolarization and dispersion of repolarization. The aim of this study was to evaluate changes in ventricular repolarization following transcatheter aortic valve implantation (TAVI). Materials and methods:The study population included 100 consecutive patients with severe AS that underwent TAVI. Electrocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Several studies have shown that QTd increased in patients with AS [15] and the increased QTd value significantly reduced after TAVI. [16,17] Similar to these studies, we also found significant reductions in QT, QTc, and QTd after three months from TAVI. However, in these studies, only QT parameters were used, and no information about the novel repolarization markers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Several studies have shown that QTd increased in patients with AS [15] and the increased QTd value significantly reduced after TAVI. [16,17] Similar to these studies, we also found significant reductions in QT, QTc, and QTd after three months from TAVI. However, in these studies, only QT parameters were used, and no information about the novel repolarization markers.…”
Section: Discussionsupporting
confidence: 86%
“…[14] Several studies showed that QTd (QT dispersion) increased in patients with AS, while TAVI was found to cause a significant reduction in QTd. [15][16][17] In addition, Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios were shown to increase in patients with severe AS. [18] However, there is no study investigating the effect of TAVI on these novel markers.…”
mentioning
confidence: 99%
“…QTD is increased in most patients with AS and these changes are weakly related to the degree of left ventricular hypertrophy [4]. Several studies have shown that increased QTD due to AS, which is associated with the risk of ventricular arrhythmia, decreases after TAVI [7,10]. Our findings also confirmed that prolonged QTD and QTcD rapidly decline after TAVI treatment, whereas SAVR slowly recovers QTD and QTcD.…”
Section: Comparison Of Qtd Between Tavi and Savrsupporting
confidence: 84%
“…The prolongation of the interval from the peak to the end of the T wave (Tpeak-Tend: TpTe) on ECG and TpTe/QT ratio, which reflects the transmural dispersion of ventricular repolarization (TDR), has also been associated with the incidence of ventricular arrhythmia [6,7]. Similar to QTD, TpTe is prolonged in patients with severe AS and immediately recovers after TAVI [8].…”
Section: Introductionmentioning
confidence: 99%